Secondary battery and electric device comprising same

By adjusting the powder conductivity of the negative electrode active material and the compaction density of the negative electrode film layer, the problems of black spots and lithium evolution in secondary batteries are solved, and better cycling and kinetic performance are achieved.

CN119852534AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311677390.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

Secondary batteries are prone to dark spots and lithium removal during use or storage, resulting in a decrease in circulation and kinetic performance.

Method used

By adjusting the powder conductivity of the negative electrode active material and the compaction density of the negative electrode film layer, a good electrical contact and conductive network between the negative electrode active material particles is ensured, thereby alleviating the SEI film generation hysteresis and gas barrier.

Benefits of technology

It effectively improves the circulation and dynamic performance of the secondary battery, reduces the dark spot phenomenon and lithium extraction problems, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852534A_ABST
    Figure CN119852534A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and a power utilization device comprising the same, the secondary battery comprises a negative electrode piece, the negative electrode piece comprises a negative electrode current collector and a negative electrode film layer, and the negative electrode film layer is arranged on at least one surface of the current collector and comprises a negative electrode active material and a conductive agent; the powder conductivity sigma of the negative electrode active material is greater than or equal to 80S / cm and less than or equal to 106S / cm; and the compaction density of the negative electrode film layer is 1.35 g / cm < 3 > to 1.50 g / cm < 3 >. The negative pole piece is beneficial to reducing the black spot phenomenon of the secondary battery and improving the cycle performance and the dynamic performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device containing the same. Background Art

[0002] In recent years, secondary batteries have been increasingly used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. Therefore, higher requirements are placed on the performance of secondary batteries.

[0003] During the use or storage of secondary batteries, due to a series of complex chemical and physical reactions inside the battery, certain failure phenomena often occur, such as black spots and lithium precipitation, which seriously reduce the performance of the secondary battery. The negative electrode active material is one of the important raw materials for secondary batteries and has a great influence on the electrical properties of secondary batteries. The failure of graphite negative electrode materials mainly occurs on the surface of graphite, which is generated in the process of electrochemical reaction between the graphite surface and the electrolyte to generate a solid electrolyte interface phase (SEI), and ultimately affects the cycle performance of the secondary battery. Therefore, it is necessary to provide a secondary battery that can improve the black spot phenomenon of secondary batteries. Summary of the invention

[0004] The present application provides a secondary battery, which has good cycle performance and kinetic performance and can reduce the black spot phenomenon on the surface of the negative electrode of the secondary battery.

[0005] The secondary battery provided in the present application comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the current collector and comprising a negative electrode active material, wherein the negative electrode active material has a compaction density of 1.5 g / cm 3 The powder conductivity σ measured under the test conditions is greater than or equal to 80S / cm and less than or equal to 106S / cm; the compaction density of the negative electrode film layer is 1.35g / cm 3 -1.50g / cm 3 .

[0006] Adjusting the powder conductivity σ of the negative electrode active material and the compaction density of the negative electrode film layer can ensure good electrical contact and conductive network between the negative electrode active material particles in the negative electrode sheet, alleviate the problem of delayed gas production caused by delayed SEI film formation in some active material particles during the formation process and the black spot defect caused by the inability of active ions to be embedded in the active material due to gas barrier, alleviate the lithium plating problem caused by the active ion content in the battery cell being greater than the acceptable amount of the negative electrode, and help improve the cycle performance and kinetic performance of secondary batteries.

[0007] In any embodiment, the powder conductivity σ is 83S / cm-104S / cm, which is beneficial to further improve the conductivity of the negative electrode active material, improve the black spot phenomenon, and enhance the cycle performance of the secondary battery.

[0008] In any embodiment, the compaction density of the negative electrode film layer is 1.40-1.50 g / cm 3 , which can further improve the energy density of secondary batteries.

[0009] In any embodiment, the negative electrode active material satisfies at least one of the following conditions:

[0010] (1) Volume distribution particle size D of the negative electrode active material V 1 is 1.4μm-3.0μm, optional is 1.7μm-2.7μm;

[0011] (2) Volume distribution particle size D of the negative electrode active material V 50 is 12μm-18μm, optional is 12.9μm-14.5μm;

[0012] (3) The particle size distribution of the negative electrode active material (D V 90-D V 10) / D V 50 is 1.3-1.8, optional is 1.35-1.70.

[0013] Control volume distribution particle size D V 1. It can reduce the excessive active sites on the surface of the negative electrode active material and the irreversible active ion consumption caused by the excessive content of small particles; it can also help improve the conductive network between the negative electrode active material particles, and also help the secondary battery to have good cycle performance and alleviate the black spot phenomenon. Control the volume distribution particle size D V 50 helps to obtain sufficient active sites, reduce the inhibitory effect on the deintercalation rate of active ions, and improve the kinetic performance of secondary batteries; controlling the particle size distribution of negative electrode active materials helps to improve the particle size distribution concentration of negative electrode active materials, reduce the side reactions of negative electrode active materials with excessively large and small particle sizes in electrochemical reactions, comprehensively improve the cycle performance and kinetic performance of secondary batteries, and further reduce the black spot phenomenon.

[0014] In any embodiment, the tap density of the negative electrode active material is 1.25 g / cm 3 -1.45g / cm 3 , optional 1.29g / cm 3 -1.41g / cm 3Adjusting the tap density of the negative electrode active material can make the negative electrode active materials of different particle sizes well dispersed in the negative electrode sheet, the negative electrode active material particles have sufficient contact sites and good electrical contact, the active ions are well embedded and released between the negative electrode active materials, and the precipitation of active ions and the black spot phenomenon of the negative electrode sheet are reduced.

[0015] In any embodiment, the specific surface area of ​​the negative electrode active material is 0.8 m 2 / g-1.4m 2 / g, optional 0.9m 2 / g-1.3m 2 Adjusting the specific surface area of ​​the negative electrode active material is beneficial to increasing the contact sites and surface active sites between the negative electrode active material particles, increasing the conductivity of the negative electrode active material and improving the transport performance of active ions, thereby improving the cycle performance of the secondary battery.

[0016] In any embodiment, the gram capacity of the negative electrode active material is 335 mAh / g-350 mAh / g, and can be optionally 340.5 mAh / g-347.5 mAh / g, thereby improving the energy density of the secondary battery and enhancing its cycle performance.

[0017] In any embodiment, the surface density of the negative electrode film layer in the negative electrode plate is 7 mg / cm 2 -15mg / cm 2 , which can increase the energy density of secondary batteries and improve the cycle performance of secondary batteries.

[0018] In any of the embodiments, the negative electrode active material includes artificial graphite.

[0019] A second aspect of the present application provides an electrical device, comprising the secondary battery of the first aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0021] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0022] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0023] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0024] Figure 5 yes Figure 4An exploded view of a battery pack according to an embodiment of the present application is shown.

[0025] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0026] Figure 7 The cycle curves of Example 2 of the present application and Comparative Example 1 are shown.

[0027] Description of reference numerals:

[0028] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0029] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0030] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0035] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0036] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions (for example, lithium ions, sodium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through.

[0037] During the formation stage of the secondary battery, the negative electrode active material and the electrolyte will undergo an electrochemical reaction to generate a solid electrolyte interface (SEI), accompanied by the generation of gas. In this process, some of the negative electrode active material particles have poor electrical contact with the surrounding particles. During the formation process, the electrochemical reaction between the graphite material and the electrolyte is not timely, and a complete SEI film cannot be formed in time, resulting in a lag in the formation of the SEI film and gas production. The gas generated by this lag cannot be discharged in time with the formation process and is retained between the negative electrode plate and the separator, hindering the charging process of the active ions in this area from escaping from the positive electrode, passing through the separator, and embedding into the negative electrode, resulting in black spot defects. This causes some of the negative electrode active materials to be unable to effectively participate in the charge and discharge cycle of the secondary battery. The content of the positive electrode active ions in the secondary battery is greater than the maximum acceptable active ion content of the negative electrode, causing some of the active ions to precipitate on the surface of the negative electrode and lose their electrical activity, resulting in a decrease in the capacity of the battery cell and rapid decay of the cycle performance.

[0038] [Secondary battery]

[0039] The present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material. The negative electrode active material has a compaction density of 1.5 g / cm 3 The powder conductivity σ measured under the test conditions is greater than or equal to 80S / cm and less than or equal to 106S / cm; and the compaction density of the negative electrode film layer is 1.35g / cm 3 -1.50g / cm 3 .

[0040] By adjusting the powder conductivity σ of the negative electrode material and the compaction density of the negative electrode film layer, the active material particles in the negative electrode sheet have good electrical contact and conductive network, which can slow down the gas production lag caused by the delayed formation of SEI film in some negative electrode active material particles during the formation process, thereby reducing the black spot defects caused by the inability of active ions to be deintercalated due to gas barrier and the lithium plating problem of secondary batteries, reducing the irreversible consumption of active ions and improving the cycle performance and kinetic performance of secondary batteries.

[0041] In this paper, the powder conductivity σ is the value of the negative electrode active material at a compacted density of 1.5 g / cm 3 The powder conductivity σ measured under the test conditions can be measured using methods known in the art, for example, using the following method:

[0042] At 25°C, use the FT-8100A four-probe powder test platform, refer to the four-probe method in GBT 30835-2014 for powder conductivity determination method to prepare the sample; weigh 1g of the test sample powder and place it in a cylindrical metal mold with a height of 25mm and a diameter of 12mm; press the lower electrode of the mold, and when the upper electrode is pressed to the table, the sample begins to be compressed, and the pressure is maintained for 30s so that the sample thickness is maintained at 0.147±0.002. Then, the negative electrode active material is measured by the four-probe powder method at 1.50g / cm 3 Electrical conductivity of powders at compacted density.

[0043] In some embodiments, the negative electrode active material has a compaction density of 1.5 g / cm 3 The powder conductivity σ measured under the test conditions is 83S / cm-104S / cm. In some embodiments, the negative electrode active material has a compaction density of 1.5g / cm 3 The powder conductivity σ measured under the test conditions is 85S / cm-100S / cm, 90S / cm-104S / cm, 85S / cm-104S / cm or 95S / cm-100S / cm. Adjusting the powder conductivity of the negative electrode active material helps to further improve the electrical contact between the negative electrode active material particles, improve the conductivity of the negative electrode active material, reduce the black spot phenomenon and improve the cycle performance of the secondary battery.

[0044] In some embodiments, the compaction density of the negative electrode film layer is 1.40 g / cm 3 -1.50g / cm 3 In some embodiments, the compaction density of the negative electrode film layer is 1.40 g / cm 3 -1.43g / cm 3 , 1.44g / cm 3 -1.50g / cm 3 , 1.41g / cm 3 -1.50g / cm 3 or 1.40g / cm 3 -1.45g / cm 3 In some embodiments, the compaction density of the negative electrode film layer is 1.41 g / cm 3 , 1.42g / cm 3 , 1.44g / cm 3 , 1.45g / cm 3 , 1.46g / cm 3 , 1.47g / cm 3 , 1.48g / cm 3 , 1.49g / cm 3, or the range between any two values. Adjusting the compaction density of the negative electrode film layer can further improve the energy density of the secondary battery and the diffusion channel of the active ions in the secondary battery, and improve the migration performance of the active ions; it can also improve the rapid capacity decay caused by the precipitation of active ions on the negative electrode surface due to insufficient charge and discharge capacity in the late cycle, thereby improving the cycle performance and fast charging performance of the secondary battery.

[0045] The compaction density of the negative electrode film layer has a well-known meaning in the art and can be measured by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode plate test sample with an area of ​​S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode plate. Then the weighed electrode film layer is wiped off, the weight of the negative electrode current collector is weighed, recorded as W2, and the thickness T2 of the negative electrode current collector is measured using a micrometer. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].

[0046] In some embodiments, the surface density of the negative electrode film layer is 7 mg / cm 2 -15mg / cm 2 , 8mg / cm 2 -15mg / cm 2 , 9mg / cm 2 -15mg / cm 2 , 7mg / cm 2 -13mg / cm 2 In some embodiments, the surface density of the negative electrode plate is 13.0 mg / cm 2 , 12mg / cm 2 、11mg / cm 2 、10mg / cm 2 , 9mg / cm 2 , 8mg / cm 2 , 7mg / cm 2 Or any value between the two. Adjusting the surface density of the negative electrode sheet helps to increase the energy density of the secondary battery and improve the cycle performance of the secondary battery.

[0047] In this application, the surface density of the negative electrode film layer has a well-known meaning in the art and can be tested by methods known in the art. As an example, take a cold-pressed negative electrode sheet, punch it into a small disc with an area of ​​S1, weigh it, and record it as M1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the weight of the negative electrode collector, and record it as M0. The surface density of the negative electrode film layer = (the weight of the negative electrode sheet M1-the weight of the negative electrode collector M0) / S1.

[0048] In some embodiments, the volume distribution particle size D of the negative electrode active material is V1 is 1.4 μm-3.0 μm, and can be 1.7 μm-2.7 μm, 1.8 μm-2.7 μm, 1.71 μm-2.58 μm. In some embodiments, the volume distribution particle size D of the negative electrode active material is V 1 is 1.6μm, 2.0μm, 1.2μm, 1.5μm, 1.6μm or any range between two values. Small-particle negative electrode active materials have large specific surface area and many surface active sites. It is easier to form byproducts at the active sites during the cycle, resulting in increased consumption of active ions and deterioration of cycle performance. Adjust the volume distribution particle size D of the negative electrode active material V 1 It helps to reduce the content of small particle negative electrode active materials, reduce the irreversible consumption of active ions, and improve the cycle performance of secondary batteries. At the same time, adjust the volume distribution particle size D V 1 It can further improve the diffusion channels of active ions in secondary batteries, improve the migration performance of active ions and the rapid capacity decay caused by the precipitation of active ions in the late cycle.

[0049] In some embodiments, the volume distribution particle size D of the negative electrode active material is V 50 is 12 μm-18 μm, and can be 14 μm-16.5 μm, 12 μm-14 μm, 12.9 μm-14.5 μm. In some embodiments, the volume distribution particle size Dv50 of the negative electrode active material is 12.9 μm, 13 μm, 15 μm, 16 μm, 17 μm, or a range between any two values. Adjusting the volume distribution particle size Dv50 of the negative electrode active material V 50 helps to improve the specific surface area of ​​the negative electrode active material and provide sufficient surface active sites, shorten the migration path of active ions, promote the insertion and extraction of active ions, and improve the conductivity of the negative electrode active material and the power performance of the secondary battery.

[0050] In some embodiments, the particle size distribution (D V 90-D V 10) / D V 50 is 1.3-1.8, and can be optionally 1.35-1.70, 1.35-1.60. In some embodiments, the particle size distribution of the negative electrode active material is 1.4, 1.45, 1.5, 1.55, 1.65, 1.7, 1.75 or a range between any two values. Adjusting the particle size distribution of the negative electrode active material can control the content of small particles in the negative electrode active material and make the particle size distribution of the negative electrode active material more concentrated, which is beneficial to reduce the irreversible active ion consumption caused by excessive small particle content; it also helps to improve the conductive network between the negative electrode active material particles, which can improve the cycle performance and power performance of the secondary battery.

[0051] In this application, the volume distribution particle size D of the negative electrode active material is V 10. D V 50. D V 90 is a well-known meaning in the art, which respectively represents the particle size corresponding to the cumulative volume distribution percentage of the material reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.

[0052] In some embodiments, the tap density of the negative electrode active material is 1.25 g / cm 3 -1.45g / cm 3 , optional 1.25g / cm 3 -1.35g / cm 3 , 1.29g / cm 3 -1.41g / cm 3 , 1.25g / cm 3 -1.41g / cm 3 In some embodiments, the tap density of the negative electrode active material is 1.28 g / cm 3 , 1.30g / cm 3 , 1.33g / cm 3 , 1.40g / cm 3 , 1.42g / cm 3 Or the range between any two values. When the tap density of the negative electrode active material is within a suitable range, the negative electrode active material particles with a smaller particle size can be well dispersed between the negative electrode active material particles with a larger particle size, filling the gaps between the negative electrode active material particles with a larger particle size, and increasing the contact sites between the negative electrode active material particles, which can not only improve the conductivity of the negative electrode active material particles, but also help the embedding and extraction of active ions in the negative electrode active material, reduce the precipitation of active ions and the black spot phenomenon of the negative electrode sheet, and thus improve the cycle performance of the secondary battery.

[0053] Herein, tap density has a meaning known in the art, and can be measured using methods known in the art. For example, it can be measured using a powder tap density tester (such as Dandong Better BT-301) with reference to GB / T 5162-2006.

[0054] In some embodiments, the specific surface area of ​​the negative electrode active material is 0.8 m 2 / g-1.4m 2 / g, optional 0.9m 2 / g-1.3m 2 / g, 0.95m 2 / g-1.1m 2 / g, 0.97m 2 / g-1.1m 2 In some embodiments, the specific surface area of ​​the negative electrode active material is 1.0 m 2 / g, 1.05m 2 / g, 1.1m 2 / g, 1.15m 2 / g, 1.2m 2 / g, 1.25m 2 / g, 1.30m 2 / g, 1.35m 2 / g or the range between any two values. Adjusting the specific surface area of ​​the negative electrode active material is beneficial to improving the overlap between the negative electrode active material particles, increasing the contact sites and surface active sites of the negative electrode active material, improving the conductivity of the negative electrode active material and the transport performance of active ions, and improving the cycle performance and power performance of the secondary battery.

[0055] In this article, the term "specific surface area" refers to the sum of the total surface area of ​​all particles per gram of material. The specific surface area of ​​graphite materials can be measured using instruments and methods known in the art. For example, the specific surface area of ​​the negative electrode active material can be measured by a specific surface area analyzer (American Micromeritics TriStar3020) using a nitrogen adsorption / desorption method with reference to the specific surface area determination method of GB / T 19587-2017: the negative electrode active material is dried in a vacuum drying oven and placed in a sample tube, and measured in the analyzer.

[0056] In some embodiments, the gram capacity of the negative electrode active material is 335 mAh / g-350 mAh / g. Herein, the term "gram capacity" refers to the ratio of the capacity that can be released by the graphite material to the mass of the graphite material. Generally speaking, the higher the gram capacity, the more conducive it is to improving the energy density of the secondary battery.

[0057] In some embodiments, the gram capacity of the negative electrode active material is 340.5 mAh / g-347.5 mAh / g, for example, 344.7 mAh / g, 345.5 mAh / g, 344.9 mAh / g, 345.9 mAh / g, which helps to improve the energy density of the secondary battery and enhance the cycle performance of the secondary battery.

[0058] The gram capacity can be measured by any method known in the art. For example, the graphite negative electrode active material sample, the conductive agent carbon black, and polyvinylidene fluoride (PVDF) can be fully stirred and mixed in an appropriate amount of solvent NMP at a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode, the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed at a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF 6 Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. Assemble into a CR2430 button cell in an argon-protected glove box. At 25°C, first discharge the button cell prepared above to 0.005V at a constant current of 0.05C, then discharge to 0.005V at a constant current of 10μA, let stand for 5 minutes, and record the first cycle discharge capacity of the button cell; then charge to 2.0V at a constant current of 0.1C, and record the charging capacity of the button cell. The ratio of the charging capacity of the button cell to the mass of the graphite negative electrode active material sample is the gram capacity of the graphite negative electrode active material.

[0059] In the present application, the negative electrode active material can be prepared using a method comprising the following steps:

[0060] Providing raw materials; processing the raw materials to obtain a precursor; graphitizing the precursor to obtain a graphitized product; and demagnetizing to obtain a negative electrode active material.

[0061] In some embodiments, the feedstock includes at least one of petroleum coke, needle coke, and pitch coke.

[0062] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.

[0063] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.

[0064] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.

[0065] In some embodiments, the feedstock comprises petroleum coke.

[0066] Petroleum coke has excellent anisotropy, which is conducive to the preparation of low-graphitization, low-expansion graphite materials, which is conducive to the long cycle life of the battery. At the same time, petroleum coke has high compaction density and high gram capacity, which is conducive to improving the energy density of the battery. In addition, the source of petroleum coke is more extensive, which is conducive to industrial production.

[0067] The above-mentioned raw materials usually include at least one of mosaic, regional and fiber structures. Usually, based on the morphological characteristics and isochromatic zone size of the coke material under a polarizing microscope, isochromatic zone microstructures with a size less than 30 μm are judged as mosaic, isochromatic zone microstructures with a size greater than 30 μm are judged as regional, and anisotropic strip-shaped isochromatic zones are judged as fiber structures.

[0068] In some embodiments of the present application, based on the total volume of the raw material structure, the volume proportion of the mosaic and regional structures in the raw material is greater than or equal to 60%, and can be optionally 65%-80%.

[0069] In this application, the volume proportion of mosaic and regional structures in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with cement, flatten it, and place it on the stage to align the focus, calibrate the microscope, and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the mosaic-type and regional-type structure optical tissues by the total number of statistical testing points as the volume proportion of the mosaic-type and regional-type structures in the raw material.

[0070] In some embodiments, crushing is the process of reducing the particle size of the raw material, and the raw material can be crushed by any mechanical device such as a crusher, a mechanical mill, etc.

[0071] Grading is the process of adjusting the particle size distribution of the raw material to obtain a precursor that meets the particle size requirements. The particle size and particle size distribution of the precursor can be regulated by adjusting the grading frequency and the air intake. In some embodiments, the grading frequency during the grading process is 40 Hz-50 Hz, and the air door opening is 20%-70%.

[0072] In some embodiments, the D of the precursor V50Particle size is 10.0μm~25.0μm.

[0073] In some embodiments, the D of the precursor V 50 The particle size is 10.0 μm, 13.0 μm, 15.0 μm, 17.0 μm, 20.0 μm, 23.0 μm, 25.0 μm or any numerical range therebetween.

[0074] In some embodiments, the particle size distribution (D V 90-D V 10) / D V 50 is 1.05-1.75.

[0075] In some embodiments, the particle size distribution (D V 90-D V 10) / D V 50 is 1.05, 1.15, 1.25, 1.35, 1.45, 1.55, 1.65, 1.75 or any range therebetween.

[0076] In some embodiments, the tap density of the precursor is 0.5 g / cm 3 ~2g / cm 3 .

[0077] In some embodiments, the tap density of the precursor is 0.5 g / cm 3 , 0.8g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 1.8g / cm 3 Or any range of values ​​in between.

[0078] In some embodiments, a low-temperature carbonization treatment may be performed before the graphitization treatment. In some embodiments, the temperature of the low-temperature carbonization is 900° C.-1300° C., and the time of the low-temperature carbonization is 24 hours-240 hours.

[0079] In some embodiments, the temperature of the low temperature carbonization may be selected to be 900° C., 1000° C., 1100° C., 1200° C., 1300° C., or any range therebetween.

[0080] In some embodiments, the low-temperature carbonization time may be 24 h, 50 h, 75 h, 100 h, 150 h, 200 h, 240 h, or any range therebetween.

[0081] Herein, the term "graphitization treatment" refers to the heat treatment process of carbon materials, which is the process in which the carbon materials transform from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth under high temperature.

[0082] In some embodiments, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0083] In some embodiments, the maximum power of the graphitization treatment is 70%, 75%, 80%, 85%, 90% or any range of values ​​therebetween of the rated power of the graphitization treatment equipment. It is understood that the graphitization treatment equipment refers to any device capable of graphitization treatment, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace and other devices. Among them, the rated power of graphitization treatment equipment produced by different manufacturers may be different, and can be selected according to actual conditions.

[0084] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000-32000 W. The graphitization treatment time can be 10h-30h, and can be optionally 15h-25h.

[0085] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000-30000 W. The graphitization treatment time can be 30h-50h, and can be optionally 40h-50h.

[0086] The maximum power of the graphitization treatment used in this application needs to be lower than the rated power of the graphitization treatment equipment to achieve uniformity of the thermal field during the graphitization treatment process.

[0087] In some embodiments, the maximum power of the graphitization process may be 20,000W-25,000W.

[0088] In some embodiments, the maximum power of the graphitization process may be 20000 W, 21000 W, 22000 W, 22500 W, 23000 W, 23500 W, 24000 W, 25000 W, or any range therebetween.

[0089] By controlling the maximum power of the graphitization treatment, the degree of graphitization of the graphite material during the heat treatment process can be effectively controlled. While the internal area of ​​the graphite material particles is highly graphitized, a uniform disordered layer is formed on the surface of the body, which is beneficial to improving the cycle stability of the secondary battery.

[0090] In some embodiments, during the graphitization treatment, the maximum power is maintained at a constant power for a period of 10 hours to 50 hours. In some embodiments, the maximum power is maintained at a constant power for a period of 10 hours, 13 hours, 16 hours, 19 hours, 22 hours, 25 hours, 28 hours, 31 hours, 33 hours, 36 hours, 39 hours, 42 hours, 45 hours, 48 ​​hours, 50 hours, or any range of values ​​therebetween.

[0091] In some embodiments, the temperature of the graphitization treatment is 2600°C to 3000°C.

[0092] In some embodiments, the temperature of the graphitization treatment is 2600° C., 2700° C., 2800° C., 2900° C., 3000° C., or any range therebetween.

[0093] The appropriate graphitization treatment temperature and the appropriate graphitization treatment time are not likely to cause excessive rearrangement of the precursor, resulting in a high specific surface area of ​​the graphite material after graphitization and deterioration of high-temperature performance; it can also effectively improve the graphitization degree of the graphite material, thereby facilitating the simultaneous improvement of the high-temperature storage and cycle life of the secondary battery.

[0094] [Negative electrode]

[0095] As an example of a negative electrode sheet, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0096] In some embodiments, the negative electrode film layer includes a graphite material prepared by the method described in the first aspect of the present application, thereby enabling the secondary battery to have both good cycle performance and kinetic performance.

[0097] In some embodiments, the negative electrode active material includes one of artificial graphite, natural graphite, soft carbon, hard carbon and mesophase carbon microbeads. In some embodiments, the negative electrode active material includes artificial graphite.

[0098] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned graphite materials. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0099] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0100] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0101] In some embodiments, the negative electrode plate further includes a conductive agent, which includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0102] In some embodiments, the conductive agent includes carbon black. In some embodiments, the conductive agent includes carbon nanotubes. In some embodiments, the conductive agent includes carbon black and carbon nanotubes. The conductive agent has a wide range of sources and excellent conductivity, which is beneficial to controlling the preparation cost of the secondary battery and improving the conductivity of the negative electrode sheet.

[0103] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0104] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0105] [Positive electrode]

[0106] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0107] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0108] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0109] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0110] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0111] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0112] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0113] [Electrolytes]

[0114] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0115] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0116] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0117] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0118] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0119] [Isolation film]

[0120] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0121] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0122] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0123] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0124] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0125] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0126] In one embodiment of the present application, a secondary battery is provided.

[0127] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1The secondary battery 5 is a square structure as an example.

[0128] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0129] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0130] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0131] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0132] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0133] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0134] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0135] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0136] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0137] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0138] Example

[0139] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0140] 1. Test Method

[0141] 1. Particle size test of powder

[0142] Determination method: Refer to GB / T 19077-2016 particle size distribution laser diffraction method, use Master Size 3000 laser particle size analyzer from Malvern Instruments Ltd., UK, to obtain volume distribution particle size D V 10. D V 50. D V 90 and D V 1.

[0143] 2. Powder conductivity test of powder

[0144] At 25°C, the FT-8100A four-probe powder test platform was used to prepare the sample according to the four-probe method in GBT 30835-2014 on the determination of powder conductivity. 1 g of the test sample powder was weighed and placed in a cylindrical metal mold with a height of 25 mm and a diameter of 12 mm. The lower electrode of the mold was pressed, and the sample began to be compressed when the upper electrode was pressed to the table. The pressure was maintained for 30 seconds so that the sample thickness was maintained at 0.147±0.002. Then, the carbon material was measured by the four-probe powder method at 1.50 g / cm 3 Powder conductivity under powder compaction.

[0145] 3. Specific surface area test of powder

[0146] Referring to the specific surface area determination method of GB / T 19587-2017, the specific surface area of ​​the negative electrode active material was measured by a specific surface area analyzer (Micromeritics TriStar 3020, USA) using a nitrogen adsorption / desorption method: the negative electrode active material was dried in a vacuum drying oven and then placed in a sample tube and measured in the analyzer.

[0147] 4. Tap density test of powder

[0148] Referring to GB / T 5162-2006 and GB / T 24533-2009, a powder tap density tester (such as Dandong Better BT-301) was used to measure the tap density with the following measurement parameters: vibration frequency 250±15 times / min, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.

[0149] 5. Negative electrode active material gram capacity test

[0150] The gram capacity can be measured by any method known in the art. For example, the graphite negative electrode active material sample, the conductive agent carbon black, and polyvinylidene fluoride (PVDF) can be fully stirred and mixed in an appropriate amount of solvent NMP at a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode, the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed at a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF 6Dissolve in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. Assemble into a CR2430 button cell in an argon-protected glove box. At 25°C, first discharge the button cell prepared above to 0.005V at a constant current of 0.05C, then discharge to 0.005V at a constant current of 10μA, let stand for 5 minutes, and record the first cycle discharge capacity of the button cell; then charge to 2.0V at a constant current of 0.1C, and record the charging capacity of the button cell. The ratio of the charging capacity of the button cell to the mass of the graphite negative electrode active material sample is the gram capacity of the graphite negative electrode active material.

[0151] 6. Compaction density test of negative electrode film layer

[0152] Use an electronic balance to weigh the negative electrode sheet test sample with an area of ​​S, record the weight as W1, and use a micrometer to measure the thickness of the negative electrode sheet T1. Then wipe off the weighed electrode sheet film layer, weigh the weight of the negative electrode current collector, record it as W2, and use a micrometer to measure the thickness of the negative electrode current collector T2. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].

[0153] 7. High temperature cycle performance test

[0154] At 60°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.

[0155] 8. Black spot test

[0156] At 25° C., the batteries of the above embodiments and comparative examples were charged at a constant current of 0.33C to a voltage of 3.65V, and then disassembled in a drying room to observe whether there were black spots on the surface of the negative electrode plate;

[0157] (1) The total area of ​​black spots / total area of ​​the negative electrode piece is ≤1%, and the area of ​​black spots in a single electrode piece / area of ​​a single electrode piece is ≤8% is defined as a first-level black spot;

[0158] (2) 1% < total area of ​​black spots / total area of ​​negative electrode ≤ 3%, or 8% < area of ​​black spots in a single electrode / area of ​​a single electrode ≤ 15% is defined as secondary black spots;

[0159] (3) The total area of ​​black spots / total area of ​​the negative electrode is greater than 3%, or the area of ​​black spots in a single electrode is greater than 15%, which is defined as level 3 black spots.

[0160] 9. Dynamic performance test

[0161] At 25°C, the secondary battery was charged to 3.65V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.50V at a constant current of 0.33C, and its actual capacity was recorded as C0.

[0162] Then the secondary battery is charged with 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, constant current to 3.5V or 0V negative electrode cut-off potential (whichever is reached first), and it needs to be discharged to 2.5V at 1C0 after each charging is completed. The negative electrode potential corresponding to charging to 10%, 20%, 30%, ..., 80% SOC (State of Charge) at different charging rates is recorded, and the charging rate-negative electrode potential curve under different SOC states is drawn. After linear fitting, the charging rate corresponding to the negative electrode potential of 0V under different SOC states is obtained. The charging rate is the charging window under the SOC state, which is recorded as C 10%SOC , C 20%SOC , C 30%SOC , C 40%SOC , C 50%SOC , C 60%SOC , C 70%SOC , C 80%SOC According to the formula (60 / C 10%SOC +60 / C 20%SOC +60 / C 30%SOC +60 / C 40%SOC +60 / C 50%SOC +60 / C 60%SOC +60 / C 70%SOC +60 / C 80%SOC )×10% to calculate the charging time T of the secondary battery from 10% SOC to 80% SOC (under the premise that the secondary battery does not precipitate lithium), in minutes. The shorter the charging time, the better the fast charging performance of the secondary battery.

[0163] 2. Preparation Method of Negative Electrode Active Material

[0164] 1. Preparation of negative electrode active material H1

[0165] The petroleum coke with mosaic and regional structures accounting for 67% is coarsely crushed, and then the coarsely crushed materials are crushed and screened, and the screened materials are shaped and graded. During the grading process, the classifier induced air frequency is controlled to remove fine powder (powder with volume distribution particle size Dv50 of 3μm-7μm) accounting for 25% of the total mass of the petroleum coke raw materials to obtain a precursor. Among them, the volume distribution particle size Dv50 of the precursor is 15.2μm, and the particle size distribution (Dv90-Dv10) / Dv50 is 1.45.

[0166] The precursor is graphitized in an Acheson furnace at a graphitization temperature of 2800°C and a maximum power of 21000W. After maintaining a constant power treatment of the maximum power for 48 hours, the surface temperature of the graphite crucible of the Acheson furnace is cooled to 250°C to obtain an intermediate product.

[0167] The intermediate product obtained is sieved and demagnetized to obtain graphite H1, a negative electrode active material.

[0168] 2. Preparation of negative electrode active material H2

[0169] The preparation process of negative electrode active material H2 is similar to that of H1, except that:

[0170] The same raw materials are used, and after crushing, shaping and grading, without removing fine powder during the grading process, the negative electrode active material H2 is obtained after the same graphitization and screening and demagnetization steps.

[0171] 3. Preparation of negative electrode active material H3

[0172] The preparation process of negative electrode active material H3 is similar to that of H1, except that:

[0173] During the classification process, fine powder accounting for 16% of the total mass of the petroleum coke raw material is removed, and then the negative electrode active material H3 is obtained through the same graphitization and screening and demagnetization steps.

[0174] 4. Preparation of negative electrode active material H4

[0175] The preparation process of negative electrode active material H4 is similar to that of H1, except that:

[0176] During the classification process, fine powder accounting for 20% of the total mass of the petroleum coke raw material is removed, and then the active material H4 is obtained through the same graphitization and screening and demagnetization steps.

[0177] 5. Preparation of negative electrode active material H5

[0178] The preparation process of negative electrode active material H5 is similar to that of H1, except that:

[0179] During the classification process, fine powder accounting for 35% of the total mass of the petroleum coke raw material was removed, and then the active material H5 was obtained through the same graphitization and screening and demagnetization steps.

[0180] The negative electrode active materials H1-H5 were tested using the above method, and the parameter test results are shown in Table 1:

[0181] Table 1

[0182]

[0183] 3. Preparation of secondary batteries

[0184] Example 1

[0185] 1) Preparation of negative electrode sheet

[0186] The prepared negative electrode active material, conductive agent carbon black Super P, thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber were mixed in a mass ratio of 96:1:1.2:1.8, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, and cutting. The compacted density of the negative electrode sheet is 1.50g / cm 3 , surface density is 9.50mg / cm 2 .

[0187] 2) Preparation of positive electrode

[0188] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder polyvinylidene fluoride are mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone is added. The system is stirred under the action of a vacuum mixer until it becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, and cutting. The compacted density of the positive electrode sheet is 2.5g / cm 3 , surface density is 19.5mg / cm 2 .

[0189] 4) Preparation of electrolyte

[0190] In an argon atmosphere glove box with a water content of less than 10 ppm, 8% lithium hexafluorophosphate (LiPF 6 ), 2% vinylene carbonate (VC), 30% ethylene carbonate (EC), 30% ethyl methyl carbonate (EMC), and the remainder is supplemented with diethyl carbonate (DEC) to 100%, and the corresponding electrolyte is obtained by mixing.

[0191] 5) Isolation film

[0192] A polypropylene film is selected as the isolation film.

[0193] 6) Preparation of secondary batteries

[0194] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0195] Examples 2 to 6 and Comparative Examples 1 to 4

[0196] The preparation methods of the secondary batteries of Examples 2 to 6 and Comparative Examples 1 to 4 are similar to the preparation method of the secondary battery of Example 1, but the negative electrode active materials and the preparation parameters of the secondary battery are adjusted. The results of the test of the secondary batteries prepared in Examples 1 to 6 and Comparative Examples 1 to 4 using the above method are shown in Table 2 below:

[0197] Table 2

[0198]

[0199] It can be seen from Examples 1 to 6 that the powder conductivity σ of the negative electrode active material is greater than or equal to 80 S / cm and less than or equal to 106 S / cm, and the compaction density of the negative electrode film layer is 1.35 g / cm 3 -1.50g / cm 3 The black spot phenomenon is effectively improved, and the secondary battery has both good cycle times and charging time.

[0200] It can be seen from Examples 1-2 and Comparative Example 1 that the compaction density of the negative electrode film layer is lower than 1.35 g / cm 3 When the negative electrode active material particles are exposed to the sun, the electrical contact between the negative electrode active material particles becomes poor and the energy density of the secondary battery is low, resulting in a decrease in the number of cycles of the secondary battery and an increase in the black spot phenomenon. Figure 7 The cycle curves of Example 2 and Comparative Example 1 are shown. It can be seen that the cycle performance of the secondary battery of Example 2 is significantly better than that of Comparative Example 1.

[0201] It can be seen from Examples 1-2 and Comparative Example 2 that the compaction density of the negative electrode film layer is higher than 1.50 g / cm 3 When the compaction density is increased, the electrical contact between the active materials of the negative electrode film layer is improved, which can improve the black spot phenomenon; however, the increase in compaction density leads to a significant deterioration in kinetics and a significant extension of the charging time, which in turn leads to rapid decay in the late cycle and reduces the cycle performance of the secondary battery.

[0202] It can be seen from Examples 1 to 6 and Comparative Example 3 that the negative electrode active material in Comparative Example 3 has a relatively high fine powder content, resulting in a powder conductivity σ of less than or equal to 80 S / cm; although the fine powder in the active material can improve the electrical contact between the active materials, too much fine powder will clog the pores, significantly prolonging the charging time, and further leading to rapid decay in the late cycle, affecting the cycle performance of the secondary battery.

[0203] It can be seen from Examples 1 to 6 and Comparative Example 4 that the fine powder content in the negative electrode active material in Comparative Example 4 is relatively small, resulting in its powder conductivity σ being greater than 106 S / cm, the electrical contact and conductive network between the negative electrode active materials being deteriorated, and the irreversible consumption of active ions in the secondary battery being increased, affecting the charge and discharge performance and capacity of the secondary battery, resulting in a significant decrease in the number of cycles and the generation of serious black spot phenomenon.

[0204] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the current collector and comprising a negative electrode active material, characterized in that: The negative electrode active material has a compaction density of 1.5 g / cm 3 The powder conductivity σ measured under the test conditions is 80S / cm-106S / cm; and the compaction density of the negative electrode film layer is 1.35g / cm 3 -1.50g / cm 3 .

2. The secondary battery according to claim 1, characterized in that: The powder conductivity σ is 83S / cm-104S / cm.

3. The secondary battery according to claim 1 or 2, characterized in that: The compaction density of the negative electrode film layer is 1.40 g / cm 3 -1.50g / cm 3 .

4. The secondary battery according to any one of claims 1 to 3, characterized in that: The negative electrode active material satisfies at least one of the following conditions: (1) Volume distribution particle size D of the negative electrode active material V 1 is 1.4μm-3.0μm, optional is 1.7μm-2.7μm; (2) Volume distribution particle size D of the negative electrode active material V 50 is 12μm-18μm, optional is 12.9μm-14.5μm; (3) The particle size distribution of the negative electrode active material (D V 90-D V 10) / D V 50 is 1.3-1.8, optional is 1.35-1.

70.

5. The secondary battery according to any one of claims 1 to 4, characterized in that: The tap density of the negative electrode active material is 1.25 g / cm 3 -1.45g / cm 3 , optional 1.29g / cm 3 -1.41g / cm 3 .

6. The secondary battery according to any one of claims 1 to 5, characterized in that: The specific surface area of ​​the negative electrode active material is 0.8 m 2 / g-1.4m 2 / g, optional 0.9m 2 / g-1.3m 2 / g.

7. The secondary battery according to any one of claims 1 to 6, characterized in that: The gram capacity of the negative electrode active material is 335 mAh / g-350 mAh / g, and can be optionally 340.5 mAh / g-347.5 mAh / g.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: The surface density of the negative electrode plate is 7 mg / cm 2 -15mg / cm 2 .

9. The secondary battery according to any one of claims 1 to 8, characterized in that: The negative electrode active material includes artificial graphite.

10. An electrical device, characterized in that: A secondary battery selected from any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery and preparation method thereof

    CN102237553A

  • Vehicle-mounted and energy-storage lithium ion battery cathode material and preparation method thereof

    CN103560247A

  • Laminated flexible-package battery

    CN106920919A

  • Negative electrode material with high temperature resistance, preparation method of negative electrode material and application of negative electrode material in lithium-ion battery

    CN107919472A

  • Negative electrode active material composite, negative electrode pole piece, secondary battery, battery module, battery pack and electric device

    CN117154022A

Cited By

  • Secondary battery and electric apparatus containing same

    EP4807811A1